Causes and consequences of adult laryngotracheal stenosis. (7th October 2014) - Gelbard, Alexander; Francis, David O.; Sandulache, Vlad C.; Simmons, John C.; Donovan, Donald T.; Ongkasuwan, Julina
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Laryngotracheal stenosis (LTS) is largely considered a structural entity, defined on anatomic terms (i.e., percent stenosis, distance from vocal folds, overall length). This has significant implications for identifying at‐risk populations, devising systems‐based preventive strategies, and promoting patient‐centered treatment. The present study was undertaken to test the hypothesis that LTS is heterogeneous with regard to etiology, natural history, and clinical outcome. Study Design Retrospective cohort study of consecutive adult tracheal stenosis patients from 1998 to 2013. Methods Subjects diagnosed with laryngotracheal stenosis (ICD‐9: 478.74, 519.19) between January 1, 1998, and January 1, 2013, were identified. Patient characteristics (age, gender, race, follow‐up duration) and comorbidities were extracted. Records were reviewed for etiology of stenosis, treatment approach, and surgical dates. Stenosis morphology was derived from intraoperative measurements. The presence of tracheostomy at last follow‐up was recorded. Results One hundred and fifty patients met inclusion criteria. A total of 54.7% had an iatrogenic etiology, followed by idiopathic (18.5%), autoimmune (18.5%), and traumatic (8%). Tracheostomy dependence differed based on etiology (P < 0.001). Significantly more patients with iatrogenic (66%) and autoimmune (54%) etiologies remained tracheostomy‐dependent compared to traumatic (33%) or idiopathic (0%) groups. On multivariate regression analysis, each additional point on Charlson Comorbidity Index was associated with a 67% increased odds of tracheostomy dependence (odds ratio 1.67; 95% confidence interval 1.04–2.69; P = 0.04). Conclusions Laryngotracheal stenosis is not a homogeneous clinical entity. It has multiple distinct etiologies that demonstrate disparate rates of long‐term tracheostomy dependence. Understanding the mechanism of injury and contribution of comorbid illnesses is critical to systems‐based preventive strategies and patient‐centered treatment. Level of Evidence 4. Laryngoscope, 125:1137–1143, 2015